Strengthening Branding and Digital Marketing in Presto Balap Milkfish MSMEs as an Effort to Increase Product Added Value - Arie Rachmat; Vivi Anggraini; Arifa Husna Amalia; Shafa Vania Putri (Journal of Islamic Economy and Community Engagement, 2026)
Guidelines Digital transformation in the micro, small, and medium enterprises (MSMEs) sector is a strategic need in facing market competition in the digital economy era. However, there are still many MSMEs that are not able to utilize digital technology optimally, especially in branding and marketing aspects. This study aims to analyze the strengthening of branding and digital marketing in Presto Noah Milkfish MSMEs in Mendiro Hamlet, Ngawi Regency, as an effort to increase product added value. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Mentoring activities are focused on creating and managing marketplace accounts, mapping business locations through Google Business Profile, preparing Cost of Production (HPP), packaging innovations using the vacuum packaging system, and implementing the QRIS digital payment system. The results of the study show that strengthening brand identity through more professional logos and packaging, as well as the use of digital marketing, is able to increase business visibility, expand market reach, and strengthen consumer trust in products. In addition, marketing digitalization also encourages the increase of digital literacy of business actors and supports the sustainability of MSMEs based on local potential. This study concludes that digital branding and marketing are effective strategies in increasing product added value and the competitiveness of MSMEs in the midst of digital economy dynamics.